Pattern extraction for programming performance evaluation using directed apriori - Mohamad Mohsin, Mohamad Farhan; Zaiyadi, Mohd Fairuz; Md Norwawi, Norita; Abd Wahab, Mohd Helmy (2009)
Computer programming is taught as a core subject in Information Technology related studies.It is one of the most essential skills which each student has to acquire.However, there is still a small number of students who are unable to write a program well. Several researches indicated that there are many factors which can affect student programming performance.Thus, the objective of this paper is to investigate the significant factors that may influence students programming performance using information from previous student performance.Since data mining data analysis able to discover hidden knowledge in database, a programming dataset which comprises information about performance profile of Bachelor of Information Technology students of Faculty of IT, Universiti Utara Malaysia in the year 2004-2005 were explored using data mining technique.The dataset consists of 421 records with 70 mixture type of attributes were pre-processed and then mined using directed association rule (AR) mining algorithm namely apriori.The result indicated that the student who has a programming experience in advanced before starts learn programming in university and scored well in Mathematics and English subject during SPM were among the factor that contributes to a good programming grades.